2021
DOI: 10.3389/fonc.2021.744250
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic Features Associated With HPV Status on Pretreatment Computed Tomography in Oropharyngeal Squamous Cell Carcinoma Inform Clinical Prognosis

Abstract: PurposeThere is a lack of biomarkers for accurately prognosticating outcome in both human papillomavirus-related (HPV+) and tobacco- and alcohol-related (HPV−) oropharyngeal squamous cell carcinoma (OPSCC). The aims of this study were to i) develop and evaluate radiomic features within (intratumoral) and around tumor (peritumoral) on CT scans to predict HPV status; ii) investigate the prognostic value of the radiomic features for both HPV− and HPV+ patients, including within individual AJCC eighth edition-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
1
16
1
Order By: Relevance
“…The selection of the 50th percentile of DPT in place of the 50th percentile of ADC PT (even though strongly correlated with HPV status as well) seemed to confirm that the perfusion-free diffusion coefficient, D, may better reveal the specific HPV-positive tumor characteristics related to cell density and tissue microstructure, compared to ADC, as also supported by other investigators [36,38]. The increase in inverse difference moment of ADC in HPV-positive patients indicated a higher homogeneity of metastatic lymph nodes, in accordance with a number of previous studies based on both CT and PET imaging, which reported an increase in homogeneity of CT density and in FDG uptakes [13][14][15][16]39]. This can be explained considering the different mechanisms of carcinogenesis between HPV-positive and HPV-negative HNSCCs, the former being more homogeneously triggered by the HPV infection, the latter being the consequence of more intricate genetic alterations attributable to the toxic effect of alcohol drinking and tobacco smoking [12,33].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The selection of the 50th percentile of DPT in place of the 50th percentile of ADC PT (even though strongly correlated with HPV status as well) seemed to confirm that the perfusion-free diffusion coefficient, D, may better reveal the specific HPV-positive tumor characteristics related to cell density and tissue microstructure, compared to ADC, as also supported by other investigators [36,38]. The increase in inverse difference moment of ADC in HPV-positive patients indicated a higher homogeneity of metastatic lymph nodes, in accordance with a number of previous studies based on both CT and PET imaging, which reported an increase in homogeneity of CT density and in FDG uptakes [13][14][15][16]39]. This can be explained considering the different mechanisms of carcinogenesis between HPV-positive and HPV-negative HNSCCs, the former being more homogeneously triggered by the HPV infection, the latter being the consequence of more intricate genetic alterations attributable to the toxic effect of alcohol drinking and tobacco smoking [12,33].…”
Section: Discussionsupporting
confidence: 86%
“…Multiple studies have already developed CT-based radiomic signatures for predicting HPV status [13][14][15][16], while only a few studies focused on MRI-based radiomics, taking advantage of the better soft-tissue contrast of morphological sequences than CT, and of functional information provided by diffusion-and perfusion-weighted techniques [17][18][19]. The clinical utility of DWI in discriminating HPV-positive from HPV-negative patients and its superiority with respect to morphological sequences, i.e., T2-weighted and/or contrastenhanced T1-weighted imaging, has been recently suggested by the investigation of Suh et al [19] and supported by previous correlation studies between DWI and histopathology in HNSCC [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since radiomics is an innovative quantitative imaging analysis technique that utilizes quantitative metrics through high-throughput extraction, numerous researches have investigated its predictive value of HPV status for OPSCC. In a study by Bolin et al, radiomic biomarkers on CT images were applied to predict HPV status of OPSCC patients using a linear discriminant analysis machine-learning classi er, performing well in both training (AUC = 0.84) and validation cohorts (AUC = 0.70) (13). Beomseok et al reported that MRI phenotyping, based on Radiomics, can also discriminate between HPV positive and negative OPSCC, and may serve as a potential imaging biomarker (14).…”
Section: Discussionmentioning
confidence: 99%
“…Since imaging is acquired at the macroscopic scale, radiomics allows for interrogating not only the disease regions of interest, but also surrounding structures such as the peri-tumoral region ( 11 ). Radiology images offer the opportunity to be used in conjunction with machine learning to build diagnostic, prognostic and predictive models ( 12 - 14 ).…”
Section: Introductionmentioning
confidence: 99%